ICD-11 Prolonged Grief Disorder, Physical Health, and Somatic Problems: A Systematic Review - James Cunningham; Mark Shevlin; Catalina Cerda; Eoin McElroy (Clinical Psychology in Europe)
[Background] Since Prolonged Grief Disorder’s (PGD) inclusion as a mental health disorder in the ICD-11 in 2018, much of the peer-reviewed research has focused on its prevalence, assessment, and co-occurrence with other mental health disorders. There is also emerging research literature on the association between PGD and physical and somatic health outcomes. In light of this, the objective of this review was to identify and summarise the extant research on the association between PGD, and outcomes related to physical health and somatic complaints among bereaved individuals. [Method] A systematic review utilized electronic databases (Web of Science, MEDLINE, Cochrane Library, PsycINFO) up to October 10, 2023. Included were cohort and cross-sectional studies since 2018 exploring links between ICD-11 PGD and physical/somatic health outcomes. Two researchers independently identified eligible studies meeting inclusion/exclusion criteria, employing quality assessment instruments to evaluate methodological rigor. [Results] From the 418 articles that were initially screened, 18 met the inclusion criteria. The studies reported significant associations between PGD and physical health, somatic symptom distress, insomnia severity, blood pressure, bodily distress syndrome, chronic physical diseases, and poor- caregiver health profiles. [Conclusion] Out of the 18 studies eligible for analysis, 13 (72%) established a significantly strong or moderate association between PGD and physical or somatic illness, highlighting the intricate nature of this connection. Further research is required to assess the breadth of physical and somatic health problems associated with PGD and to understand the psychological and biological mechanisms that underpin these observed relationships.